Exploring the Perspectives of Trade Professionals on E-commerce for Order Management - Mahto, Navin; Maheshwari, Dinesh Kumar (Academia Journal of Research and Innovation, 2026)
Background: E-commerce is an important means of trade, which allows quicker and efficient order management, particularly in such developing nations as Nepal. It is critical to understand the view of trade professionals regarding the online management of orders in order to embrace the concept of digital transformation in trade practices. Methods: This research surveyed 51 trade professionals in Nepal in order to determine how they saw e-commerce in order management. The data were obtained with the help of structured questionnaires and analyzed with descriptive statistics and independent samples t-test in order to compare the two genders. Findings: The majority of the respondents perceived e-commerce systems to be useful in easing order handling, accelerating cross-border orders, minimizing shipping mistakes, boosting tracking and communication, as well as customer satisfaction. Even though there was a marginally better positive perceptions among females as compared to the males, the difference was not significant. Conclusion: Nepalese trade practitioners overall are positive opinions about e-commerce using to manage orders, and there are no significant differences between the genders. These results indicate the need to encourage digital solutions in enhancing trade efficiency and competitiveness in Nepal.